Effect of the hydrophobic phase on interfacial phenomena of surfactants, proteins, and particles at fluid interfaces. (December 2021) - Bergfreund, Jotam; Bertsch, Pascal; Fischer, Peter
Abstract: The hydrophobic or oil phase in fluid mixtures is often given little attention in interfacial experiments and emulsion design. This has been the cause for significant inconsistencies in the scientific literature, as experiments were often performed at arbitrary oils, which impeded the reproducibility and comparability as well as hampers the pathway to a generic description. Here, we summarize the effect of the oil phase on the adsorption, assembly, and interfacial rheology of surfactants, proteins, and particles at fluid interfaces and the resulting influence on emulsions. Furthermore, we provide experimental guidelines for using oils in interfacial experiments, aiming to harmonize results and protocols in interfacial science.